Sistem Informasi Administrasi Rukun Warga Berbasis Website Menggunakan Metode Rapid Application Development (RAD) - Dadan Herdiansah; Winarsih (STMIK Budi Darma, 2023)
RW or Rukun Warga are social institutions that are legalized and supported by the government to uphold and uphold the fundamental principles that form the basis of life in Indonesia, namely mutual cooperation and a sense of kinship, with the aim of making a positive contribution to improving the smooth implementation of various government activities. development and social functions. the manual method is the process currently implemented in letter management, meaning that residents attend the RT head to approve the letter and then hand it over to the kelurahan. Considering this, a system planning is needed which can be called a web-based Rukun Warga Administration Information System, and making this website requires various references and previous research to become reference material for improving similar systems in the future. Due to the limitations of RW (Rukun Warga), there must be an appropriate solution that can help the community to provide good services, including creating a system. The system itself can be understood as a group or a number of elements or several components that are connected and interact with each other with the aim of achieving a goal, in another sense it can be seen as a unit composed of interconnected elements, forming a larger system that is supported by various elements. Considering this, we need a system design that can be referred to as an information system that operates through a web platform. Web design uses the Unified Modeling Language (UML) Rapid Application Development (RAD) method, with the PHP programming language, and testing uses Black Box Testing. The results of this research have succeeded in meeting user needs in developing a web-based community association administration information system. This website is designed to overcome problems often faced by RT and RW parties so far. With this website, RT and RW performance can be more efficient in carrying out their duties in serving residents. The various features provided on this website, such as submitting cover letters, RT and RW financial reporting, as well as collecting data on residents in RT and RW, will help increase the effectiveness and accuracy of their administrative work